Capital Flow Reversals and Currency Crises: Do Capital Flow Types Matter? - Mengting Zhang; Andreas Steiner; Jakob de Haan; Haizhen Yang (Center for Economic Studies and ifo Institute (CESifo), 2024)
We analyse how reversals of several types of capital flows impact currency crises in emerging market and developing economies. Estimates of logit models show that reversals of (equity and debt) portfolio flows significantly increase the likelihood of currency crises in emerging market economies. In developing economies, reversals of portfolio debt flows and banking flows have a significant positive impact on currency crises. Finally, our results suggest that countries with mature financial systems and fixed exchange rate regimes are less likely to experience a currency crisis after a capital flow shock. The mediating role of capital account liberalization varies by country type.
Keywords: E44; E51; F34; F41; 330; capital flow reversals; currency crises; event study approach; logit models; domestic financial factors